(untitled) (Applied Biological Research, 2019)
A laboratory-based experiment was conducted to study the effect of tea leaf based diets on the growth and reproduction intwo dominant earthworm species (Pontoscolex corethrurus and Drawida assamensis) of tea plantations in Tripura (India). Among the four different diets [soil (S); soil-tea leaf (ST); soil-cow dung (SC) and soil-tea leaf-cow dung (STC)], P. corethrurus maintained significant higher growth rate than native species, D. assamensis in each diet. Growth rate was highest in SC for both P. corethrurus (11.35 mg worm-1 day-1) and D. assamensis (10.70 mg worm-1 day-1). Cocoon appeared in all the experimental culture pots, except in ST with D. assamensis. In both the species, growth rate was lowest in S and ST. Among all the experimental diets, both the earthworm species produced highest number of cocoons in SC diet for the whole experimental period (150 days). The rate of juvenile production in P. corethrurus (0.82 juvenile worm-1 week-1) was significantly higher than those in D. assamensis (0.28 juvenile worm-1 week-1). The experiment clearly indicates that for vermiculture of these two geophagous earthworm species, cow dung is preferred to tea leaf-based diets probably because of rich content of polyphenols in latter.